Companion reader on violence against women - Renzetti, Claire M.; Edleson, Jeffrey L.; Kennedy Bergen, Raquel (Sage Publications, 2012)
"This reader is intended to be bundled with several books on our list that coincide with courses on domestic violence and family violence. The primary book is Renzetti, Sourcebook on Violence Against Women as well as Barnett, Family Violence Across the Lifespan. The book will contain 20 articles selected by the editors to compliment the Sourcebook. It will be organized in three parts: Theoretical Issues, Types of Violence and Prevention, and Direct intervention. Because the research in this area is fast moving, it is important for students to be aware of the latest findings and trends. The reader will help faculty feel confident that students are getting exposed to the latest research on violence against women. The editors will also provide a one page summary of highlights and lessons for each article in the reader. They will also develop discussion questions for all the articles in the reader"--